Strategy of measuring bradykinin and kallidin and their concentration in plasma and urine - Hilgenfeldt, Ulrich; Linke, Rosita E.; Riester, Udo; König, Wolfgang; Breipohl, Gerhard (Analytical biochemistry, 1995)
Bradykinin (BK) and kallidin (KAL) derivatives containing a Cys residue instead of a Ser residue at positions 6 and 7, respectively [BK(Cys6), KAL(Cys7)], were synthesized. These derivatives were linked to BSA via the Cys residue by a heterobifunctional cross-linker. The coupling product containing a kinin with both free N- and C-terminal ends was used as immunogen. We obtained highly sensitive and specific antisera, simultaneously directed against both free ends. The radioimmunoassay for BK displays a sensitivity of 0.5-60 fmol BK at a dilution of 1:80,000 with 125I-BK(Tyr8) as tracer. Des-Arg9-BK, [BK(1-8)], displayed the highest cross-reactivity in the amount of 24%. Des-Arg1-BK and smaller molecular weight fragments display a crossreactivity of less than 0.1%. The cross-reactivity of the BK antiserum with KAL is approximately 4%. In presence of 125I-KAL(Tyr9) the radioimmunoassay for KAL displays a sensitivity of 2 to 200 fmol KAL at an antiserum dilution of 1:80,000. The cross-reactivity with BK is 0.02%. KAL(Hyp4), BK(Hyp3), and des-Arg10-KAL [KAL(1-9)] show a cross-reactivity of 6.3, 4.9, and 2.4%. All other natural kinin derivatives show a cross-reactivity of less than 1%. Both assays were used to measure BK and KAL concentrations in blood and urine of humans after extraction and HPLC separation. The BK plasma level is 1.97 (SD 0.54) pg/ml. The KAL plasma level is 81.0 (SD 14.3) pg/ml, indicating that KAL instead of BK is a circulating peptide. In urine, the BK level is 16.3 pg/ml. As in plasma these values were much lower than those of urinary KAL (2120 pg/ml). These data suggest that kallidin may be either filtered or generated in the kidney, namely in the connecting tubuli, where high amounts of tissue kallikrein are known to be present. Furthermore, it appears that the small amounts of BK in urine are generated by conversion of KAL by urinary aminopeptidase B. In conclusion, highly selective antisera against BK and KAL were raised against both peptides coupled in the center of the molecule. These antibodies display a binding that is simultaneously directed against both free ends. With the radioimmunoassays for both peptides, high concentrations of KAL and low concentrations of BK are found in plasma and urine.